Molecular analysis and clinical significance of hemoglobin Quong Sze in Huizhou city, Southern China - Zeyan Zhong; Zhiyang Guan; Dina Chen; Guoxing Zhong; Hailin He; Kunxiang Yang; Jianhong Chen (Elsevier, 2023)
Objective: Hemoglobin Quong Sze (Hb QS) is one of the most common non-deletional α-thalassemia (α-thal), which is prevalent in the Southern Chinese population. However, there are still few comprehensive researches on the molecular characterization of Hb QS. So it is important to find out appropriate diagnosis and characterization of Hb QS carrier for genetic counseling. Materials and methods: A hematological screening including hematological indices and hemoglobin analysis was performed in 113,400 individuals from Huizhou city, Southern China. Then, suspected thalassemia carriers were detected by a suspension-array system and DNA sequencing for α- and β-thal. Results: In our study, we identified 521 subjects who were Hb QS carriers, including fourteen different genotypes. Among them, 445 Hb QS heterozygotes showed a decrease in the mean corpuscular hemoglobin (MCH), 16 compound heterozygotes for Hb QS/α+-thal presented mild thalassemia, 28 Hb QS in combination with --SEA/αα manifested as Hb H disease, varying clinical symptoms from only moderate anemia to severe anemia and requiring blood transfusion, and 29 double heterozygotes for Hb QS and β-thal behaved as β-thal trait. The mean corpuscular volume (MCV) and MCH were significantly reduced and no Hb H peak could be detected in one patient with Hb H-Hb QS and β-thal. Meanwhile, we identified two homozygous Hb QS carriers, who showed mild to moderate anemia and increased Hb A2 level but negative results from a sequencing analysis for the first time. Additionally, Comparison of hematological parameters among the major four genotype groups showed significant differences in most box-whisker plots. Conclusion: People who originated from Huizhou city showed many genotypes and diversity in the clinical manifestations of Hb QS carriers. This study enlarges the mutation spectrum of α-thal and emphasizes that reliable detection of the gene mutations is important for genetic counseling. It also strengthens the prevention and control of thalassemia.